Ekonomi Biru Kepulauan Riau Berkelanjutan: Tantangan, Peluang dan Langkah Strategik Berbasis Kolaborasi Pentahelix - Muhammad Alfarizi (Jurnal Archipelago, 2025)
Indonesia, as a global maritime axis nation, has a long history in sea trade that has shaped its cultural diversity. With its rich biodiversity and thousands of islands, Indonesia, particularly the Riau Islands, is a megabiodiverse country with strategic maritime potential. The national economy focuses on the concept of the "blue economy," with the Riau Islands expected to pioneer sustainable blue economy practices. The complex challenges faced by the Riau Islands in achieving the blue economy vision require multisectoral involvement. The pentahelix concept can be a solution to address issues of ecosystem degradation, suboptimal resource management, and limited community capacity, through collaboration between the government, industry, academia, society, and media. This study aims to evaluate the potential and challenges of the blue economy in the Riau Islands Province, as well as strategic solutions through pentahelix actor involvement. The study employs a Systematic Review method using 55 articles indexed in Scopus, Sinta Indonesia, and Google Scholar. The results show significant potential in the fisheries and marine tourism sectors, contributing notably to employment and welfare. Serious challenges such as biological pollution, climate change, and marine pollution require government strategies, including technology and renewable energy policies. Higher education institutions play a crucial role in supporting the blue economy through research and human resource development. Marine business actors and coastal tourism, with the support of society and media, are responsible for maintaining and supporting the conception of a sustainable blue economy. Synergy among all parties is key to realizing a sustainable and inclusive blue economy vision in the Riau Islands Province.